PENDEKATAN PEMBELAJARAN PAI BERBASIS KITAB KUNING PADA KELAS TAKHASSUS KITAB DI PONDOK PESANTREN DARUSSALAM PURWOKERTO - Dheazeta Sugandi, Amanda; Nur Atika, Faizah (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study aims to describe the learning approach of Islamic Religious Education (PAI) based on *kitab kuning* (classical Islamic books) applied in the *takhassus kitab* class at Darussalam Islamic Boarding School, Purwokerto. *Kitab kuning* is a treasure trove of classical Islamic knowledge that holds historical, philosophical, and methodological value in shaping a deep religious understanding. In the pesantren context, *kitab kuning* not only serves as a source of knowledge but also as a means of character building and fostering critical thinking among students. This research uses a descriptive qualitative approach with data collected through observation, in-depth interviews with instructors, and documentation of the learning process. The findings show that teachers in the *takhassus kitab* class apply several learning approaches, namely the rational approach (logical reasoning toward texts), holistic approach (the integration of all aspects of Islamic education with individual needs), functional approach (relating the book’s content to students’ daily lives), and historical approach (contextualizing the texts with the development of the times). The use of classical books such as Fathul Mu’in, Mauizatul Mu’minin, and Tafsir Jalalain serves as the main medium in broadening students’ religious knowledge. These approaches not only enhance students’ classical Arabic literacy skills but also shape individuals with integrity, knowledge, and a strong Islamic foundation, who are ready to contribute to society